Reformation of Dryland Management for Supporting Food-Self Sufficiency - ABDULLAH ABAS IDJUDIN; SETIARI MARWANTO (Indonesian Center for Agriculture Land Resource Development, 2008)
Dryland areas in Indonesia which have not yet managed intensively as an agriculture land cover 12.90 million ha. These areas are not well managed due to low growing index, especially in Java Island. The lack and the weakness of dryland management in Indonesia causing degradation of soil function and influencing the effort to raise people welfare. Entering the third Millenium era, the paradigm and conception of natural resources management, including reformation of dryland management are needed to be renewed. Based on bio-physic factors, moderate to high potential dryland cover 5.09 ha and low potential dryland cover 7.81 ha. Environmental physical constraint can be overcome both by short and long program in order to support food-self sufficiency stabilization. Short program is coordinated efforts to build productive dryland agriculture using technology and new innovation through integrated plant and land resources management. Long program is the continuation and extension of short program, and other effort to enhance food productivity through optimizing dryland resources utilization technologies (soil erosion control, smallponds establishment, water distribution management, and seeding system) and organizational. Food production of 11.34 x 106 t dryland rice and 6.91 x 106 t grain per year can be gained through the reformation of dryland management. Reformation of dryland management is absolutely needed to support and stabilize food-self sufficiency in Indonesia, in order to release our dependency on food import from abroad.